The burden of aerobic bacterial nosocomial infections, associated risk factors and antibiotic susceptibility patterns in a surgical site in Ethiopia: A systematic review - Tsegaye Alemayehu (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Nosocomial infection is an infection that acquired after exposure of patients to hospital for 48-72 hrs, but not present during admission. Surgical site infection is among the leading nosocomial infection that acquired after operation or admission. This review aims to determine the burden of NI in surgical site infection in Ethiopia systematically. Among a 167 mean of clinically suspected patients samples 9-92% were culture-confirmed with a mean of 70.125 and median 67. Seven studies identified 49.3-100% of culture-confirmed infection as SSI; two studies reported BSI 2.2 & 20.8 percent and one study declare UTI as 29.8 percent among 77 cultures confirmed and one study not reported about infection identified. Ward type, type of operation, wound type, being a male, site of a wound, age ≥ 51, diabetes mellitus, anaemia, antibiotic usage after surgery, 11-15 days preoperative hospital stay, postoperative hospital stay; surgical procedure, urinary catheter, mechanical vent, IV catheter, longer duration from admission to discharge, longer duration of preoperative and preoperative prophylaxis identified as potential risk factors. S. aureus and CoNS is among the leading gram-positive bacterial isolate and E. coli, Klebsiella spp, Proteus spp and P. aeruginosa are among gram-negative organisms that isolated from eight studies in Ethiopia.